The The Relationship between Career Understanding and Career Decision-Making among Ninth-Grade Students in Samarinda - Nur Anisa; Muslimin Nulipata; Indo Sennang (Reforma: Jurnal Pendidikan dan Pembelajaran, 2026)
Career understanding is an individual’s ability to comprehend and process information related to career development. This study aims to investigate the relationship between career understanding and career decision-making among ninth-grade students of Junior High School 7 Samarinda. The research employed a quantitative associative correlational approach. The study population consisted of 270 students, and the sample was determined to be 159 students. Data were collected through a Likert-scale questionnaire distributed to the participants. The data analysis was conducted using the Spearman rank correlation test with the assistance of SPSS version 25. The results revealed a significance value of 0.000, which is smaller than α = 0.05. This indicates that the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. The findings demonstrate that there is a statistically significant relationship between career understanding and career decision-making. Therefore, it can be concluded that students’ ability to understand careers plays an important role in shaping their career decisions, highlighting the need for effective career guidance from schools and educators.